Updating land information systems created using unconventional approaches - Mireille Biraro; Prof. Jaap Zevenbergen; Dr. Berhanu Kefale Alemie (African Journal on Land Policy and Geospatial Sciences, 2022)
Many are the suggestions on how to develop a new land information system or evaluate how successful is the existing system. However, guidance about how the created system can be kept up to date is shallowly mentioned in the literature while it is the key feature for its sustainability. This paper is part of an extensive research done regarding the updating of land information systems that were created using unconventional approaches during systematic land registration. For these systems, huge database are created in a short period during the initial registration. To minimize uncertainties that may be in the updating phase, a framework was developed and presented in this paper. A refined traditional approach for system design was used in the development of this framework. The design requirements were extracted from literature and they were refined basing on the responses of land experts from nine case-study countries. These refined requirements were used to develop the updating framework and its validation was done by experts in the use of unconventional approaches in land registration. The developed framework explains what to consider in the updating to ensure the registration of changes in land records. The framework is composed of ‘dimension’ which is a group of parameters related to each other; ‘parameters’ of land information system that are worthy to consider in the updating and the ‘requirements’ describing how to design these parameters to ensure that changes in land records are being registered.